2017
DOI: 10.1002/jcsm.12218
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, a modulator of musculoskeletal health in chronic kidney disease

Abstract: The spectrum of activity of vitamin D goes beyond calcium and bone homeostasis, and growing evidence suggests that vitamin D contributes to maintain musculoskeletal health in healthy subjects as well as in patients with chronic kidney disease (CKD), who display the combination of bone metabolism disorder, muscle wasting, and weakness. Here, we review how vitamin D represents a pathway in which bone and muscle may interact. In vitro studies have confirmed that the vitamin D receptor is present on muscle, descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 166 publications
(285 reference statements)
0
69
1
9
Order By: Relevance
“…testosterone, vitamin D, and parathyroid hormone). 49,50 However, in the present study, we found that an antiosteoporotic drug, ALN at low doses, could effectively reverse the impaired effects of Dexa on the muscle hypertrophy and the regenerative capacity via SIRT3 down-regulation in vitro and muscle degeneration therapy in vivo, suggesting that ALN may be provided as a novel potential remedy for steroid myopathy in the clinic in the future.…”
Section: Discussionmentioning
confidence: 46%
“…testosterone, vitamin D, and parathyroid hormone). 49,50 However, in the present study, we found that an antiosteoporotic drug, ALN at low doses, could effectively reverse the impaired effects of Dexa on the muscle hypertrophy and the regenerative capacity via SIRT3 down-regulation in vitro and muscle degeneration therapy in vivo, suggesting that ALN may be provided as a novel potential remedy for steroid myopathy in the clinic in the future.…”
Section: Discussionmentioning
confidence: 46%
“…Chronic kidney disease, for example, is prevalent in approximately 50% of all patients with HF, and CKD itself has been associated with wasting, because, very similar to HF, inflammation is involved in mediating skeletal muscle wasting in these patients. 67 Indoxyl sulfate induces mitochondrial dysfunction in models with CKD. 65 Like in HF, it has been difficult to suppress muscle wasting in patients with CKD.…”
Section: Co-morbidities Of Heart Failurementioning
confidence: 99%
“…66 Like in osteopenia development mentioned earlier, vitamin D acts a as a modulator of musculoskeletal health in patients with CKD. 67 Indoxyl sulfate induces mitochondrial dysfunction in models with CKD. This uraemic toxin is known to accelerate skeletal muscle atrophy, and therefore, indoxyl sulfate may be a potential target for mitrochondrial-targeted intervention in CKD-induced muscle atrophy.…”
Section: Co-morbidities Of Heart Failurementioning
confidence: 99%
“…Vitamin D 3 öncelikle deride sentezlenir ve karaciğerde hidroksillenerek 25 (OH) vitamin D'yi oluşturur (7)(8)(9)(10). 1,25 (OH) vitamin D, böbreklerde bir hidroksilasyon işlemi daha geçirerek aktif metabolik formuna dönüşür (7,8,11).…”
Section: Introductionunclassified
“…Erişkin yaşlarda patognomonik bulgusu bulunmamaktadır (11,13,16). Sıklıkla halsizlik, yorgunluk, duygu-durum bozukluğu, kaslarda huzursuzluk hissi, ağrı ve kramp tarzı belirtiler gösterebilir (1,3,10). D vitamini yetersizliğine bağlı oluşan osteomalazi kliniğinde genellikle lomber bölgeden başlayarak pelvis, uyluk, sırt ve kostaları içeren yaygın ağrılar görülür (3,14).…”
Section: Introductionunclassified